Leveling (down) the playing field: performance diminishments and fairness in sport - Holmen, Sebastian Jon (Journal of medical ethics, 2023)
The 2018 eligibility regulation for female competitors with differences of sexual development (DSD) issued by World Athletics requires competitors with DSD with blood testosterone levels at or above 5 nmol/L and sufficient androgen sensitivity to be excluded from competition in certain events unless they reduce the level of testosterone in their blood. This paper formalises and then critically assesses the fairness-based argument offered in support of this regulation by the federation. It argues that it is unclear how the biological advantage singled out by the regulation as an appropriate target for diminishment, is relevantly different from other biological advantages that athletes may enjoy, and specifically that Sigmund Loland’s recent attempt to drive a wedge between heightened levels of blood testosterone and other biological advantages fails. The paper also suggests that even if heightened blood testosterone levels do differ relevantly from other types of biological advantage, the regulation is further challenged by studies indicating that athletes with blood testosterone at the high end of the normal range have a competitive advantage over athletes with blood testosterone levels at the low end of it. Finally, the paper contends that the premises of the fairness-based argument do not unequivocally support the conclusion that DSD athletes with heightened levels of testosterone should diminish those levels, since, just as powerfully, they support allowing athletes with normal levels of testosterone to use performance-enhancing drugs in the name of fairness.